Biosafety and differentially expressed genes analysis of melanoma cells treated with cold atmospheric plasma. Issue 6 (15th March 2022) - Zhao, Lihong; Yan, Cong; Kong, Shuzhen; Jia, Tao; Chu, Zhaowei; Yang, Li; Wu, Jian; Geng, Songmei; Guo, Kun
Abstract: Cold atmospheric plasma (CAP) has attracted increasing attention due to its anti‐bacterial and anti‐tumor effects. Melanoma is an aggressive malignancy with increasing incidence rate and poor prognosis. Evaluating cell viability, apoptosis rate and reactive species injection efficiency of melanoma cells and human keratinocyte cells (HaCaT) treated with CAP to analyze biological safety of CAP. RNA‐sequencing (RNA‐seq) of A875 cells before and after treatment was performed to further explore the anti‐tumor mechanism of CAP. CAP had a more significant biological effect on melanoma cells than HaCaT cells by inhibiting proliferation and promoting apoptosis. RNA‐sequencing analysis showed that besides MAPK and p53 apoptotic signaling pathways, necroptosis and autophagy also played important roles in CAP‐induced melanoma cells death. CAP can selectively kill melanoma cells and has good biosafety cytologically. Besides apoptosis, CAP can induce cell death via autophagy and necroptosis. Abstract : In this study, we focused on different biological effects of cold atmospheric plasma (CAP) on melanoma cells and HaCaT cells to explore the biosafety of CAP, combining the reactive species injection efficiency and tumor cell physiological characteristic system. Subsequently, RNA‐sequencing analysis was used to comprehensively elucidate the differences in the expression of apoptosis‐related genes in melanoma cells treated by CAP. We identified that the MAPK pathway and p53 pathway played main roles in apoptosis, and found that necroptosis and autophagy were also involved in CAP anti‐tumor effect.